Pengaruh Free Cash Flow, Capital Intensity, dan Firm Size terhadap Financial Distress - Nabil Muzhaffar; Ati Sumiati; Muhammad Yusuf (LPPM Universitas Negeri Jakarta, 2026)
This study analyzes the effect of Free Cash Flow, Capital Intensity, and Firm Size on Financial Distress risk through the financial health level of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. Using purposive sampling, transform and outlier 184 companies with 449 observations were selected and analyzed through panel data regression using EViews 13. The results show that Free Cash Flow and Firm Size have a negative and significant effect on Financial Distress risk, while Capital Intensity has a positive effect, mediated through corporate financial health. These findings suggest that management should optimize free cash flow, leverage firm size efficiently, and plan asset investment in a measured and productivity-oriented manner to reduce the risk of Financial Distress.